Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3141/2308-07
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Travel Time Prediction considering the Effects of Weather

Abstract: Reliable travel time prediction enables both road users and system controllers to be well informed about future conditions on roadways so that pretrip plans and traffic control strategies can be made to reduce travel time and relieve traffic congestion. The objective of this research was to use traffic and weather data from multiple data sources to develop an integrated model that could predict travel times under various weather conditions, especially severe weather conditions. Prediction models are compared, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Autocorrelation analysis describes the correlation degree between two times i, j of time series X, which is in the range of [21,1]. The random time series with a total of J observations is divided into J 2 1 pairs, that is, (…”
Section: Choice Of State Vectormentioning
confidence: 99%
“…Autocorrelation analysis describes the correlation degree between two times i, j of time series X, which is in the range of [21,1]. The random time series with a total of J observations is divided into J 2 1 pairs, that is, (…”
Section: Choice Of State Vectormentioning
confidence: 99%
“…K-Nearest Neighbour (KNN) was used to predict travel times from two sources of data (vehicle detectors and toll collection systems) with an improvement of the matching process [10]. KNN could be also used to predict travel times under different weathers [11]. In general, those methods can be tailored to specific sites of interest, but may require long training processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, to the best of the authors knowledge, most of studies in this area have 30 considered only traffic related variables in order to develop a model for travel time prediction. 31 However, other variables such as weather condition could have significant impact on the travel 32 time (Qiao et al, 2012;Rakha et al, 2012), which is infrequently investigated in travel time 33 prediction studies. Nookala showed that inclement weather condition could increase the traffic 34 congestion and travel time, since the capacity of highway decreased in inclement weather, while 35 the traffic demand does not change (Nookala, 2006).…”
Section: Introductionmentioning
confidence: 99%